2018
DOI: 10.1002/ece3.4110
|View full text |Cite
|
Sign up to set email alerts
|

Functional traits associated with plant colonizing and competitive ability influence species abundance during secondary succession: Evidence from subalpine meadows of the Qinghai–Tibetan Plateau

Abstract: It is widely recognized that colonists and competitors dominate early and late succession, respectively, with selected species having different colonizing and competitive abilities. However, it remains unknown whether colonizing and competitive ability can determine species abundance directly over succession. The data for five key functional traits were collected (photosynthesis rate, leaf turgor loss point, leaf proline content, seed mass, and seed germination rate), which are direct indicators of plant compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Many plant traits have been documented to predict plant responses to environmental changes or disturbances, such as specific leaf area (SLA), leaf chemical composition, relative growth rate (RGR), photosynthetic pathway, life cycle, plant height, architecture, resprouting and seed traits, all of which can be used as good indicators of ecosystem health (Lavorel & Garnier, 2002; Lavorel et al, 2011; Zhang, et al, 2018a). There are also several studies that have investigated how functional traits vary across successional stages (Prach et al, 1997; Schleicher et al, 2011; Zhang et al, 2018b; Chang & Turner, 2019) and the relationship between plant traits and plant–plant interactions with ecosystem functions and properties (Díaz et al, 1999; Conti & Díaz, 2013; Soliveres et al, 2015; Gaitán et al, 2017). However, to our knowledge, how livestock grazing affects interactions among plant species with a different successional role across a grazing gradient has never been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Many plant traits have been documented to predict plant responses to environmental changes or disturbances, such as specific leaf area (SLA), leaf chemical composition, relative growth rate (RGR), photosynthetic pathway, life cycle, plant height, architecture, resprouting and seed traits, all of which can be used as good indicators of ecosystem health (Lavorel & Garnier, 2002; Lavorel et al, 2011; Zhang, et al, 2018a). There are also several studies that have investigated how functional traits vary across successional stages (Prach et al, 1997; Schleicher et al, 2011; Zhang et al, 2018b; Chang & Turner, 2019) and the relationship between plant traits and plant–plant interactions with ecosystem functions and properties (Díaz et al, 1999; Conti & Díaz, 2013; Soliveres et al, 2015; Gaitán et al, 2017). However, to our knowledge, how livestock grazing affects interactions among plant species with a different successional role across a grazing gradient has never been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Such responses depend on their ability to colonize and to compete (Cadotte, 2007;Connell & Slatyer, 1977;Swaine & Whitmore, 1988). Tree responses thus depend on the competition-colonization trade-offs among the species present (Huston & Smith, 1987;Muscarella et al, 2017;Zhang, Qi, & Liu, 2018). In nature, tree species' strategies typically appear scattered along a conceptualized "colonization-competition axis" representing a broad range of competition and dispersal abilities and strategies (Adler et al, 2014;Salguero-Gómez et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In deforested lands with grassland cover, native trees can accelerate spontaneous succession. Pioneer species dominate the first stages of succession over non-pioneer species; some studies have observed a higher survival rate for non-pioneer species due to their richer seed bank and competence abilities [ 54 , 62 ]. Some morphological traits (i.e., height) or the number of individuals in a species provide information on vegetation dynamics, such as which species groups were the first invaders, whether there are facilitation or competition processes, or future trends.…”
Section: Secondary Succession Dynamic: Deterministic or Stochastic Processes?mentioning
confidence: 99%
“…The germination rate was negatively correlated with species abundance in the early stages and negatively in the late stages of the non-altered site. These results are related to the replacement of pioneer species in the early stages with competitive species in the late stages [ 54 , 62 ].…”
Section: Species Pool Priority Effects and Species Coexistencementioning
confidence: 99%
See 1 more Smart Citation